Nurses’ experiences of caring for people with COVID-19 in Hong Kong: a qualitative enquiry - Janita Pak Chun Chau; Suzanne Hoi Shan Lo; Simon Kwun Yu Lam; David R Thompson; Ravneet Saran; Claudia Ho Yau Leung (BMJ Open, 2021)
Objectives Nurses are the largest group of healthcare workers on the front line of efforts to control the COVID-19 pandemic. An understanding of their nursing experiences, the challenges they encountered and the strategies they used to address them may inform efforts to better prepare and support nurses and public health measures when facing a resurgence of COVID-19 or new pandemics. This study aimed to explore the experiences of nurses caring for people with suspected or diagnosed COVID-19 in Hong Kong.Design A qualitative study was conducted using individual, semistructured interviews. All interviews were audio-recorded and transcribed verbatim for thematic analysis.Setting Participants were recruited from acute hospitals and a public health department in Hong Kong from June 2020 to August 2020.Participants A purposive sample of registered nurses (N=39) caring for people with COVID-19 in Hong Kong were recruited.Results Two-thirds of the nurses had a master’s degree and over a third had 6–10 years of nursing experience. Around 40% of the nurses cared for people with COVID-19 in isolation wards and a quarter performed COVID-19-related work for 31-40 hours/week. Most (90%) had training in COVID-19 and three-quarters had experience of working in infection control teams. Six key themes emerged: confronting resource shortages; changes in usual nursing responsibilities and care modes; maintaining physical and mental health; need for effective and timely responses from relevant local authorities; role of the community in public health protection and management; and advanced pandemic preparedness.Conclusions Our study found that nurses possessed resilience, self-care and adaptability when confronting resource shortages, changing nursing protocols, and physical and mental health threats during the COVID-19 pandemic. However, coordinated support from the clinical environment, local authorities and community, and advanced preparedness would likely improve nursing responses to future pandemics.